Who did it? Perspectives on the beginning of the Neolithic in Greece - Vlachos, Dimitrios (Documenta Praehistorica, 2003)
The beginning of the Neolithic in Greece has been the focus of study by many scholars for many years, and a strong argument about it is still active. DNA analysis has shed new light on a wide spectrum of questions related to the population history of Europe and the Middle East, the beginning of the Neolithic, and the adoption of agriculture in these areas. This paper will try to chart the various theories for the beginning of the Neolithic in Greece,and the contribution of archaeogenetics to the same discussion. Subsequently, there will be an effort to give some theoretical implications for future research.
Keywords: archaeology; arheologija; mezolitik; neolitik; Grčija; Greece; arheogenetika; poljedelstvo